Association of depressive symptoms and social determinants of health in medical students of four countries - Czechia, Iran, Kenya, and Venezuela - Zimovjanová, Anna; Wekesah, Frederick Murunga; Dehghani Firouzabadi, Fatemeh; Brož, Jan; Urbanová, Jana; Mechanick, Jeffrey I; Sulbarán, Natalia; Medina, Andrea; Maranhao Neto, Geraldo A; Nieto-Martinez, Ramfis; Babagoli, Masih A; Torres, Maritza; et al. (Central European journal of public health, 2025)
OBJECTIVES: Medical students experience worse psychological well-being than the general population. Social determinants of health (SDOH) relate to conditions in which people live, work, and age and significantly influence mental health. This study examines the association between depressive symptoms and SDOH in medical students from four countries: Czechia, Iran, Kenya, and Venezuela. METHODS: An online cross-sectional survey was conducted in the spring of 2022. The questionnaire focused on depressive symptoms (using a validated psychiatric scale DASS-21 to assess mental health) and various SDOHs. RESULTS: A total of 2,033 medical students participated in the survey, with a median age of 23.0 years; 64.8% were females; 60.8% of respondents had some degree of depressive symptoms (mild-to-moderate 32.5%, severe-to-extremely severe 28.3%). Several SDOHs, such as low engagement in social life, low personal funds, and low social class, were strongly associated with severe-to-extremely severe depressive symptoms (p < 0.001), and the associations differed among countries. The prevalence of severe-to-extremely severe depressive symptoms varied significantly across the four countries, with Iran having the highest prevalence (OR = 2.1 compared to Czechia), followed by Czechia (OR = 1, reference value), Kenya (OR = 0.9), and Venezuela (OR = 0.6). CONCLUSION: The study demonstrates the high prevalence of depressive symptoms among medical students from four global regions and the significant association with specific SDOH. Notably, the variation in prevalence across countries and differential relationships with SDOH underscore the importance of considering transcultural factors in research and management to improve mental health among medical students.
Keywords: Kenya; Surveys and Questionnaires; social determinants; Social Determinants of Health; Humans; prevalence; Iran; studenti lékařství; Venezuela; Keňa; Female; mladý dospělý; dospělí; lidé; Írán; průzkumy a dotazníky; medical students; Adult; ženské pohlaví; Male; Czech Republic; Students, Medical; depressive symptoms; Cross-Sectional Studies; Young Adult; Prevalence; Depression; sociální determinanty zdraví; Česká republika; mužské pohlaví; deprese; mental health; průřezové studie